English Financial Terms in Financial Statements and Their Translations in Indonesian - Noviaty, Putu Shinta (Study Program of English Literature, 2020)
This study is about analyzing the translation of English financial terms into Indonesian. The aims of this study are to identify types of financial terms found in the English financial statements based on the basic principles and to analyze the translation techniques applied. This study applies qualitative research method. The qualitative research approach is applied as the qualitative data, English Financial statements and their translations in Indonesian is used as data source in this study. First, the types of financial terms will be analyzed by using financial theory proposed by Hermanson et all (2011) regarding four basic of financial statements. There were four types of financial terms specifically found in each category. Furthermore the analysis of data source in the source language and the target language conducted based on techniques of translation as proposed by Molina and Albir (2002), Larson (1988) to see how the techniques of translation are applied to render financial terms. There are lists of terms that could be classified into those four types of financial statements. There are seven translation techniques used by translator in translating English financial terms into Indonesian. The different types of financial terms have different scope that is different purposes and aims which are to be strived for, both in the ST and in the TT. Eventhough there are differences among types of financial types in terms of its specification, it is inevitably in translating two or more types of financial terms the translator used the same technique. Keywords : financial terms, financial statement, translation techniques